2014
DOI: 10.1080/09593330.2014.951400
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biological trickling filter systems with various packing materials for improved wastewater treatment

Abstract: Attached growth processes for wastewater treatment have significantly been improved during recent years. Their application can be extended to sustainable municipal wastewater treatment in remote locations and in developing countries for the purpose of organic matter (biochemical oxygen demand, BOD) removal and pathogenic decontamination. The aim of this study is to assess selected packing media for biological trickling filters (BTFs) and to develop a simplified model for describing the capacity of BOD removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 32 publications
0
29
0
2
Order By: Relevance
“…3 and 4, respectively. This is because the anaerobic zone was destroyed using proper flushing, by which the aerobic zone was maintained in the outer portion of the slime layer [39][40][41][42]. Therefore, in the present study after 40 days of MCTF-WWT system operation, 85-90% of COD and BOD removal efficiencies were yielded.…”
Section: Cod and Bod Removalmentioning
confidence: 81%
“…3 and 4, respectively. This is because the anaerobic zone was destroyed using proper flushing, by which the aerobic zone was maintained in the outer portion of the slime layer [39][40][41][42]. Therefore, in the present study after 40 days of MCTF-WWT system operation, 85-90% of COD and BOD removal efficiencies were yielded.…”
Section: Cod and Bod Removalmentioning
confidence: 81%
“…According to Metcalf and Eddy [22], a steady operating state in trickling filters is usually reached in about four weeks of continuous operation, although other authors have observed that the steady state for COD removal can occur anywhere from three days to seven weeks [33,34]. Naz et al evaluated different media in a trickling filter, and observed that the highest COD removal efficiency was obtained by stone (93.4%), outperforming plastic (89.4%), polystyrene (86.3%), and rubber (81.9%) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The thickness and shape of the biofilm is influenced by several environmental factors such as the type of pollutant, packing material used, ambient air and wastewater temperature, humidity, moisture content, system design, and configuration of the treatment system [13,23,137]. Wijeyekoon et al [112] reported that organic loading influenced biofilm internal microstructure as with the increased organic load that produced a compact biofilm layer with lower porosity.…”
Section: Trickling Filter Performance Issues and Solution Approachesmentioning
confidence: 99%
“…Mixing of industrial wastewater in influent during VOC degradation Anaerobic conditions in the system Try to neutralized the TF influents by using buffer materials for, e.g., calcium carbonate and dolomite Use nutrient solution, for example Ca(OH) 2 , NaOH, NaHCO 3 , and urea [13,126,129] Biofilm/Slime layer Improper media selection Uneven nutrients supply Uneven aeration High organic and hydraulic loading rates Uneven sloughing Weather Conditions Control the slime layer thickness by sloughing process Create aerobic conditions by maintaining optimum oxygen transfer rate Use good filter media that support microbial growth Use a chemical addition like ferric chloride and polymers to enhanced the growth of the slime layer and also trickling filter efficiency Use optimum oxygen levels for proper growth of bio-film Optimum amounts of nutrient solutions can be applied for microbial growth Increase the DO level of influent by recirculating the effluent Optimize the organic loading rate to maintain bio-film structure [13,23,80,[136][137][138][139][140][141][142][143] effect in TF systems. It was also observed that biofilm thickness also fluctuates seasonally and the thickness was increased in winter and decreased in summer [13,79].…”
Section: Trickling Filter Operational Problems and Proposed Solutionsmentioning
confidence: 99%
See 1 more Smart Citation